2018
DOI: 10.1097/aog.0000000000002427
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Gestational Length in Four Race–Nativity Groups, Including Somali Americans

Abstract: We report a positive disparity in preterm birth and a tendency for prolonged gestation for ethnic Somali women in Ohio. Etiologic studies in multiethnic cohorts aimed to uncover the sociobiological determinants of gestational length may lead to practical approaches to reduce prematurity in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…[41][42][43] Immigrant African women are less likely to give birth preterm than native-born black women. 44,45 All of these findings illustrate the potential role of epigenetics in preterm birth. However, genetic and epigenetic studies must include people of diverse ancestry.…”
Section: Increased Riskmentioning
confidence: 78%
“…[41][42][43] Immigrant African women are less likely to give birth preterm than native-born black women. 44,45 All of these findings illustrate the potential role of epigenetics in preterm birth. However, genetic and epigenetic studies must include people of diverse ancestry.…”
Section: Increased Riskmentioning
confidence: 78%
“…Prior publications regarding pregnancies in the Somali population have been reported from the states of Washington, Ohio and Minnesota 1,2,21 . Work from the states of Washington and Ohio discusses increased rates of late term and post-term births among Somali women, with contradictory data regarding neonatal outcomes and fetal deaths 1,2,22 . Adverse outcomes have been documented among Somali women having post term births 1,2 .…”
Section: Somali : Hispanicmentioning
confidence: 99%
“…Work from the states of Washington and Ohio discusses increased rates of late term and post-term births among Somali women, with contradictory data regarding neonatal outcomes and fetal deaths 1,2,22 . Adverse outcomes have been documented among Somali women having post term births 1,2 . The Washington State study reported increased risk for adverse obstetrical and neonatal outcomes compared with both Black and white newborns 2 .…”
Section: Somali : Hispanicmentioning
confidence: 99%
See 1 more Smart Citation
“…Women of African ancestry are also twice as likely to receive a clinical diagnosis of BV, and analyses of the vaginal microbiota reveal that they are more likely to be colonized by certain BV-associated bacteria 19 . Furthermore, African American women (though not African-born women) are nearly twice as likely to give birth preterm (<37 weeks gestation) and more than twice as likely to give birth early preterm (<34 weeks) 20,21 and vitamin D deficiency has been linked to preterm birth and small-for-gestational-age infants born to women of African ancestry 22,23 . There is an urgent need to understand and address these important health disparities and an important first step in understanding whether or not the three parameters, vitamin D status, vaginal microbiome, and preterm birth, are linked.…”
Section: Introductionmentioning
confidence: 99%